A Systematic Literature Review on Picture-Based Learning in Teaching English to Young Learners: Challenges and Solutions - Mawsally, Syadzilia Aluv; Adyuta Mahardhika (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
Picture-based learning has gained increasing attention for its potential to enhance engagement and vocabulary acquisition in English for Young Learners (EYL). However, practical implementation in early childhood education remains challenging. The study follows the PRISMA 2020 guidelines. A total of 12 relevant articles were extracted from 379 articles indexed in Scopus and Taylor & Francis (2015–2025). The sample consisted of teachers and students that used visual media or images, while articles that did not address challenges or solutions in these contexts were excluded. This study revealed the challenges faced by teachers in implementing picture-based learning include: teaching strategies and classroom management, selection of appropriate visual materials, and limitations of inclusive approaches for students with special needs. (58%) articles identified teaching strategies and classroom management (TSCM) as the main challenge due to the lack of teacher training in visual-based classroom management. To overcome these issues, the study proposed several solutions, including applying stricter criteria when selecting materials, incorporating interactive strategies based on multimodality, and applying multisensory approaches to support inclusivity. This study provides important insights for EYL teachers in optimizing the use of picture media and emphasizes the need for practical guidelines to support the needs of diverse students.